Monday

July 28, 2014

July 28, 2014

Posted by **Esther** on Tuesday, October 2, 2012 at 5:54am.

If f(x)= (2x^2 - 5x - 3) / (3-x)

find f'(-8).

- calculus -
**Damon**, Tuesday, October 2, 2012 at 6:12am2(-8)^2 = 2*64 = 128

-5(-8) = 40

-3 = -3 now add

-------------

165 = numerator

3 - (-8) = 11

so

165/11

- calculus -
**Steve**, Tuesday, October 2, 2012 at 10:30amthat's f(-8), but we want f'(-8)

f(x) = -(2x+1)

**Related Questions**

calculus - How do I solve this using the TERM BY TERM method? If f(x)= (2x^2 - ...

Maths - The 3rd term of an AP is 10 more than the first term while the fifth ...

pre-calculus - Find the designated term of the binomial expansion. 5th term of (...

Math - 3,5,-5... The first term in the sequence of #'s shown above is 3. Each ...

math - The 4th term of an AP is 3 times its first term and the 7 term exceeds ...

Mathematics-please help quick!! - The first term of the sequence is -168 and ...

math - the fourth term of an arithmetic progression is equal to 3 times the ...

Precalc - Find a formula for the nth term if... a)the 8th term is 8 and the 20th...

Maths - The 5th term of an exponential sequence is 4 and of 2nd term is 35(¡)...

arithmetic - first term and larst term of a geometric progression is 42.if the ...